Les choix des équipes pédagogiques pour la réussite des étudiants : un éclairage via la cartographie du plan réussite en licence de l’Université de Bourgogne - Cathy Perret (Revue Internationale de Pédagogie de l’Enseignement Supérieur)
This article discusses the first outcomes of a series of supportive actions introduced for first year students at the University of Burgundy under a "program for improving undergraduate students' achievement rates" funded by the Ministry of Higher Education. Based on an administrative survey, it presents a typology of actions chosen by teachers to help achievement rates of their students. The typology shows how the teaching staffs have implemented this reform and describes different conceptions of success and supports for students among teachers.